Origin of Waveguiding in Ultrashort Pulse Structured Silicon - Kaemmer, Helena; Matthaeus, Gabor; Lammers, Kim A.; Vetter, Christian; Chambonneau, Maxime; Nolte, Stefan (Laser & Photonics Reviews, 2019)
The origin of waveguiding in the bulk of silicon after sub-ps laser inscription is investigated. Locally resolved Raman measurements of waveguide cross sections and along the propagation axis reveal highly localized crystal deformations. These modifications consist of highly confined regions of silicon with a disturbed crystal structure accompanied with strain. This transformation is responsible for a local increase of the refractive index allowing localized waveguiding. On the basis of near-field measurements at an excitation wavelength of 1550 nm, the absolute value of the refractive index change is estimated to be in the range of 10 −3 .
CRIS-Team Scopus Importer:2023-04-20
Keywords: laser inscription; raman microscopy; silicon waveguide; ultrashort pulses